Strategy and Implementation in Improving the Quality of Education in Panawa Village as a Form of Community Service - Firdaus, Muhammad Irham; Robiah, Rahmatu; Auliaputri, Citra Ananda; Fadila, Dila Nurul; Razzaq, Muhammad Akmal; Rivaldi, Fazri; Sulaeman, Danil (Indonesian Journal of Community Empowerment (IJCE), 2024)
This project, carried out by KKN Tematik Universitas Garut Group 58, aimed to evaluate and enhance the quality of education in Desa Panawa. The methodology involved direct observation at several educational institutions, namely TK Al-Hidayah, SDN 01 and 02 Panawa, and SMPN 02 Pamulihan, from August 5 to July 24, 2024. The results indicate that the use of interactive and participatory teaching methods, including Play Based Learning at TK Al-Hidayah and methods that incorporate discussions and educational tools at SDN 01 and 02 Panawa, as well as the integration of technology at SMPN 02 Pamulihan, effectively improved student engagement and comprehension. This study demonstrates that cooperation among students, educators, and learners can facilitate sustained improvements in educational quality.